Current Status of Antiplatelet Therapy in Acute Coronary Syndrome - Dash, Debabrata (Cardiovascular & Hematological Agents in Medicinal Chemistry, 2015)
Antiplatelet therapy is a first-line medical treatment for patients with acute coronary syndrome (ACS). As percutaneous coronary interventions (PCI) increase in number and complexity, more patients must be treated with antiplatelet therapy for cardiovascular diseases in which arterial thrombosis plays a major role. Current anti-platelet therapy is highly effective in preventing atherothrombotic complications. Nevertheless, a significant number of patients continue to experience recurrent complications despite being properly treated, due to pharmacokinetics and interactions of drugs, genetic background and increased thrombus formation. This has lead to big research efforts to provide new antiplatelet drugs with better preventive properties without increased bleeding risk. Up to 8% of patients receiving 81 mg-dose of aspirin have significantly less platelet inhibition than those receiving higher dose. Patients with poor responsiveness to clopidogrel are at high risk of thromboembolic complications, especially in the setting of ACS and stent implantation. Several options have been proposed. Firstly, to increase loading and maintenance doses up to 600 mg and 75-mg twice daily associated with high-dose aspirin (300-325 mg). A second option would be to change from clopidogrel to new antiplatelet agents like prasugrel and ticagrelor which were investigated in large clinical trials in patients with different entities of ACS. Because of conflicting results & without large scale clinical studies, routine platelet function measurement cannot be recommended at this point of time. Prasugrel is an ADP-P2Y12 receptor inhibitor that has a faster and more consistent inhibitory effect of platelet aggregation and was shown to reduce cardiovascular mortality in the setting of ACS undergoing PCI. Subgroups with increased risk of bleeding were patients with prior stroke, age over 75 and body weight under 60 kg. In this population, prasugrel is discouraged despite its increased in efficacy. Ticagrelor binds reversibly to P2Y12 receptor. The reversibility action makes it attractive for situations when dual antiplatelet therapy needs to be interrupted. Both the drugs demonstrated superiority with respect to the primary composite endpoint. As compared to clopidogrel, both prasugrel and ticagrelor do not depend on loss-offunction genetic variants. The efficacy safety ratio of both compared to clopidogrel is better, even if both these compounds increased the risk of spontaneous major bleedings significantly. Due to lack of head-to-head comparison, potential differences between prasugrel and ticagrelor are hypothetical and both these drugs should be used according to guidelines. The novel intravenous antiplatelet cangrelor cut thrombotic complications of PCI with some increase in bleeding, a pooled analysis of the three CHAMPION(Cangrelor versus Standard Therapy to Achieve Optimal management of Platelet Inhibition) trials showed. Protease-activated-receptor 1(PAR 1) antagonist vorapaxar did not reduce the primary composite ischemic end point in TRACER (Thrombin Receptor Antagonist Clinical Event reduction in acute coronary syndrome) trial, but major bleeding and intracranial hemorrhage rates were substantially increased. Further large randomized trials would be required to decide the superiority of one agent over another and the duration of the therapy.
Keywords: platelets